2021
DOI: 10.1002/smll.202007500
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Label‐Free Cell Status Monitoring of Spheroids and Microcarriers Using Microfluidic Impedance Cytometry

Abstract: cytotoxicity assessment due to close resemblance of intercellular and cellmatrix complexities in vivo. [1][2][3] Microcarriers are bead-based 3D matrix scaffolds (≈100-400 µm in diameter) used to upscale cell culture processes in tissue engineering [4,5] and cell therapies. [6,7] As these cultures may last from several days to months, [8] real-time monitoring of spheroid/microcarrier status in a label-free and non-invasive manner is of great significance in many bioprocesses. Conventional sensors for bioreacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Besides, the cell membrane (10 nm) was modelled using the contact impedance approximation rather than the full-fidelity thin-layer geometry, which greatly simplified the numerical calculations while ensuring reliable analysis. 23,48 Additionally, organelles and biomolecules are all simplified as 2D circles (dimensions: 1 μm radius, 2 μm span) with twice the thickness of the cell membrane (20 nm), because chloroplasts have a double membrane envelope. The impedance signal can be obtained through calculating the current signal when particles move along the centreline under the stimulation of the two frequencies (i.e., 500 kHz and 6 MHz) simultaneously.…”
Section: Modelling and Simulationsmentioning
confidence: 99%
“…Besides, the cell membrane (10 nm) was modelled using the contact impedance approximation rather than the full-fidelity thin-layer geometry, which greatly simplified the numerical calculations while ensuring reliable analysis. 23,48 Additionally, organelles and biomolecules are all simplified as 2D circles (dimensions: 1 μm radius, 2 μm span) with twice the thickness of the cell membrane (20 nm), because chloroplasts have a double membrane envelope. The impedance signal can be obtained through calculating the current signal when particles move along the centreline under the stimulation of the two frequencies (i.e., 500 kHz and 6 MHz) simultaneously.…”
Section: Modelling and Simulationsmentioning
confidence: 99%
“…Quality control tests include e purity, viability, genetic stability and, immunophenotype characterization [ 278 ]. Recently, Gong et al reported a novel microfluidic approach that label-free and continuous-flow monitoring of single microcarrier using co-planar Field's metal electrodes and can be integrated into bioreactors for long-term [ 279 ]. Taken together, by employing bioreactors and microcarriers, it is expected that production costs would decrease due to improved process monitoring and quality control leading to better consistency and process efficiency, and enabling economies of scale.…”
Section: Microcarriers Design Application In Cartilage Tementioning
confidence: 99%
“…However, imagingbased detection [81][82][83][84][85][86][87][88][89][90] (Fig. 3b) and impedance-based detection [91][92][93][94][95][96][97][98] (Fig. 3c) have become progressively universal in the past decade.…”
Section: Detecting Systems For Microfluidic Flow Cytometrymentioning
confidence: 99%